What hinders healthcare professionals in promoting physical activity towards cancer patients?: The influencing role of healthcare professionals’ concerns, perceived patient characteristics and perceived structural factors - Haussmann, Alexander; Gabrian, Martina; Ungar, Nadine; Jooß, Stefan; Wiskemann, Joachim; Sieverding, Monika; Steindorf, Karen (European journal of cancer care, 2018)
Despite a large body of evidence showing that physical activity (PA) is beneficial to patients with cancer, healthcare professionals (HCPs) are promoting it too scarcely. Factors that hinder HCPs from promoting PA have remained understudied so far. Using a qualitative approach, this study aimed at a comprehensive description of influencing factors for HCPs’ PA promotion behaviour and at identifying the reasons and mechanisms behind them. Semi-structured interviews with 30 HCPs were undertaken with a focus on concerns, patient characteristics and structural factors. Answers were analysed using thematic analysis. Results revealed that HCPs had concerns regarding a physical overexertion and psychological stress for patients with cancer. A patient's physical condition and the assumed interest in PA, often derived from former PA, turned out to be the most crucial patient characteristics influencing if PA is addressed. Structural factors relevant for PA promotion pertained to in-house structures, HCPs’ workload, timing and coordination, information material for HCPs and patients and availability of exercise programs. In conclusion, this study revealed undetected concerns of HCPs and underlined the relevance of patient characteristics and structural conditions for HCPs’ PA promotion towards patients with cancer. A broader perspective is needed to assess these factors in their influence on HCPs’ PA promotion.